The Role of Strategic Management in Achieving Administrative Creativity at Prince Sattam University in Al-Kharj Governorate from the Perspective of Administrative Employees - Al-Dosari, Kholoud Ghaleb Mubarak (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to identify the role of strategic management in achieving administrative creativity among administrative employees at Prince Sattam bin Abdulaziz University in Al-Kharj Governorate. It specifically examined the impact of strategic management dimensions—environmental analysis, strategy formulation, strategy implementation, and strategic control—on administrative creativity. The study adopted a descriptive analytical methodology and used a questionnaire administered to a random sample of 291 employees out of a total population of 1,261. The findings indicated a high level of agreement on the dimensions of strategic management, with a mean score of 4.14 for both environmental analysis and strategy formulation, 4.05 for strategic control, and 3.99 for strategy implementation. The level of administrative creativity was found to be very high, with a mean score of 4.21. Results also revealed a statistically significant positive correlation between strategic management and administrative creativity. Additionally, significant differences were found based on years of experience for the sake of employees who have experience less than 5 years, while no differences were detected based on gender, age, educational qualification, or job title. Based on these findings, the study recommended developing periodic mechanisms to monitor potential challenges, organizing specialized training workshops, implementing effective financial planning, and fostering a supportive environment for creativity through both material and moral incentives.
Keywords: Strategic Management; Administrative Creativity; Environmental Analysis; Strategy Formulation; Strategy Implementation